A kinetic free mathematical model for the prediction of the KSt reduction with the particle size increase. (March 2018) - Fumagalli, Anna; Derudi, Marco; Rota, Renato; Snoeys, Jef; Copelli, Sabrina
Abstract: Even in recent years, several major industrial accidents have involved dust explosions, clearly showing the necessity of mitigating the hazard related to the presence of flammable dusts. In this respect, the K St is an experimental parameter used to design the deflagration vents aimed to protect industrial devices and silos by internal dust explosions. Even if it is measured using a standard 20 L sphere test, its determination is quite expensive and time consuming. This problem is even more severe when a target dust is processed into a plant, giving rise to different average diameters; in this case, an experimental investigation of all the different particle sizes would be advisable but very expensive. In this context, the main aim of the present paper has been to develop a kinetic-free model able to predict the K St decrease with the mean particle diameter increase for organic dusts explosions. Particularly, an order of magnitude analysis of the characteristic times of the involved phenomena has showed that, in the K St measurements, the rate determining step is usually associated to heat transfer phenomena. This evidence leads to the possibility of exploring a predictive approach for the K St determination which does not require any chemical kinetic information, the most difficult to be obtained. Therefore, once the value of K St has been measured through a standard 20 L test for a given mean particle diameter (the smallest possible), the approach proposed in this work allows for predicting the K St values for the same dust at higher average particle sizes. Such an approach has been validated by comparison with several literature data as well as with a new set of experimental results. Highlights: The deflagration index, Kst, indicates the severity of a dust explosion. Prediction of Kst reduction with the particle size increase without knowing any chemical kinetic information. The explosion controlling phenomena are related to the heat transfer (both internal and external) only. This approach implies the possibility to save a significant amount of resources.